Selected topics in nanomedicine - Chang, Thomas Ming Swi (Regenerative medicine, artificial cells and nanomedicine ;, 2014)
Nanomedicine consists of the use of nanotechnology and nanobiotechnology in medicine. There have been extensive developments in the area of nanomedicine. The scope of this book is first to discuss the origin of nanomedicine. Following this, instead of a general overview of the whole area, 22 chapters on selected topics of important areas will be described in details. Authors are selected from around the world to give a representative and international view of the activities in the area of nanomedicine.